Uso de bioativador de solo associado a diferentes coberturas vegetais e a influência nas características químicas, físicas e microbiológicas - FRANCO JUNIOR, Kleso K. S. (2017)
Most Brazilian soils present low natural fertility and, often, with unbalanced nutrient contents. The use of cover crops as green manure improves soil fertility by increasing organic matter, increasing soil CEC, decreasing water erosion and reducing fertilization costs. In addition, such use stimulates the biological fraction of the soil composed of microorganisms, which perform essential functions and beneficial to the soil as decomposition of organic matter and release of nutrients unavailable to plants. Soil bioactivators are composed of organic and carboxylic acids that increase the release of macro and micronutrients from soils to plants, among which we can highlight the bioenergetic Penergetic associated to cover plants in the chemical, physical and biological characteristics and the influence of these parameters related to coffee development. The research was conducted at Fazenda Boa Esperança, in the municipality of Serrania - MG, using cover plants associated with the bioactivator in the field, using a randomized block design, in a 4x2 factorial scheme, analyzing the chemical, physical and biological characteristics of soil and coffee plant. After tabulation, the data were submitted to analysis of variance by grouping the means by means of the Scott Knott test, at 5% probability. The results indicated that the use of cover crops associated to the bioactivation technology contribute to the improvement of the chemical characteristics (CTC, base sum, base saturation, acidity, macro and micronutrients), physical (temperature and humidity) (Phosphorus and Potassium solubilizing diazotrophic bacterium) and the growth of coffee tree branches and productivity, as well as the reduction of the nematode population (Meloidogyne and Xiphinema).